Relationship between sleep bruxism and obstrutive sleep apnea: A literature review (Research, Society and Development, 2023)
This article aimed to investigate the relationship between sleep bruxism (SB) and obstructive sleep apnea (OSA). To this end, an integrative literature review was carried out in the PubMed, Medline and Scielo databases using the keywords in the form of the following string [sleep apnea and sleep apnea obstructive and bruxism and sleep bruxism]. Articles that dealt with subjects related to the proposed theme and published from 2018 to 2023 were selected. Currently, bruxism is widely recognized as a centrally controlled phenomenon and may be related to Other conditions that cause awakenings during sleep. The consulted authors corroborate that sleep bruxism occurs in its phasic form in about one third of patients with OSA, and that body posture during sleep influences the permeability of the upper airways, due to its anatomical characteristics, which may increase the OSA occurrence. The use of medication for depression or emotional disturbances can make the condition worse, and opioids can increase the risk of central sleep apnea. The association between obstructive sleep apnea and sleep bruxism varies according to the severity of the apnea. Mild to moderate obstructive sleep apnea is related to sleep bruxism in patients at higher risk of obstructive sleep apnea. However, the relationship between BS and AOS is complex and not yet fully understood. The studies present conflicting hypotheses about the temporal causality between the two disorders and the different forms of relationship between them.